(untitled) (Eurasian Research Bulletin, 2024)
Stroke remains one of the leading causes of disability and mortality worldwide. Neurointervention, which includes a wide range of methods and technologies, has become a key area in the treatment of stroke. This article reviews the main aspects of neurointervention in stroke, its advantages, methods and development prospects. The article discusses the importance of neurointerventional methods in patients treated in the intensive care unit